2017
DOI: 10.3389/fphys.2017.01097
|View full text |Cite
|
Sign up to set email alerts
|

Aminopurvalanol A, a Potent, Selective, and Cell Permeable Inhibitor of Cyclins/Cdk Complexes, Causes the Reduction of in Vitro Fertilizing Ability of Boar Spermatozoa, by Negatively Affecting the Capacitation-Dependent Actin Polymerization

Abstract: The adoption of high-througput technologies demonstrated that in mature spermatozoa are present proteins that are thought to be not present or active in sperm cells, such as those involved in control of cell cycle. Here, by using an in silico approach based on the application of networks theory, we found that Cyclins/Cdk complexes could play a central role in signal transduction active during capacitation. Then, we tested this hypothesis in the vitro model. With this approach, spermatozoa were incubated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…We found that the targeted removal of selected ones caused the collapse of the network, while the removal of 11 randomly selected nodes in the most of the cases did not have detectable consequences on network topology. In our opinion, these data are very interesting, because they clarify the signal cascade involved in control of actin dynamic and allow to confirm our data [19] re-interpret our data from Amaral and co-workers [31], that indicated the presence of several pathways previously neglected in the male gamete physiology. Concretely, they pointed out the presence of cell cycle-related proteins, in particular of cyclin–CDK) complexes and suggested that these proteins might be remnants of the spermatogenesis with no relevant function in mature spermatozoa.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that the targeted removal of selected ones caused the collapse of the network, while the removal of 11 randomly selected nodes in the most of the cases did not have detectable consequences on network topology. In our opinion, these data are very interesting, because they clarify the signal cascade involved in control of actin dynamic and allow to confirm our data [19] re-interpret our data from Amaral and co-workers [31], that indicated the presence of several pathways previously neglected in the male gamete physiology. Concretely, they pointed out the presence of cell cycle-related proteins, in particular of cyclin–CDK) complexes and suggested that these proteins might be remnants of the spermatogenesis with no relevant function in mature spermatozoa.…”
Section: Discussionsupporting
confidence: 88%
“…Since the molecular mechanisms involved in control of actin dynamics (AD) during capacitation remains not completely understood, recently, our group carried out an in silico and in vitro study. Its results suggested that cyclin-dependent kinase (cyclin–CDK) complexes could be involved in control of this event, as demonstrated by the negative effects of a cyclin–CDK-specific inhibitor (Aminopurvalanol A) on actin polymerization with dramatic consequences on sperm capacitation and on in vitro fertilization outcome [19]. On this basis, here we developed a computational model devoted to describe the role of cyclin–CDK complexes in controlling the actin dynamic in mammalian mature spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…During capacitation, this phospholipid asymmetry is reduced by scramblase, which acts as a bi-directional carrier with little specificity, moving phospholipids in both directions (inward and outward) according to their concentration gradient [2]. As a result of the LR, sperm membranes undergo a deep rearrangement that affects their composition and their biophysical properties, increasing their fluidity and fusogenicity [28]. This process enables the extracellular protein to extract cholesterol, determining the increase in the ability of the sperm plasma membrane (PM) and the outer acrosome membrane (OAM) to fuse (fusogenicity), which is a necessary prerequisite for the acrosome reaction once the zona pellucida of the oocyte is met [2].…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K activation leads to an increase in actin polymerization; thus, the G-actin polymerizes, forming long filaments of F-actin [3]. The F-actin constitutes a barrier for the fusion between the OAM and PM and, when the capacitation progresses, the interposition of F-actin avoids their premature fusion [28,29]. In response to the physiological stimulus represented by contact with proteins of the oocyte ZP, high intracellular calcium concentrations enable the depolymerization of actin, since F-actin breakdown between the membranes is needed to allow the acrosome reaction [28].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the need of analysing live spermatozoa in a very short length of time, only CTRL, BOEC-GO and BOEC-P4 groups were analysed. FRAP experiments were performed as previously described [38,42]. Briefly, the lipophilic fluorescent molecule DilC12(3) perchlorate (ENZ-52206, Enzo Life Sciences, USA) was added (1:1000) for the last 15 min of the sperm-BOEC co-incubation.…”
Section: Evaluation Of Sperm Membrane Fluidity By Fluorescence Recovery After Photobleaching (Frap) Analysis [Escriba Aquí]mentioning
confidence: 99%